Unintended pregnancy and maternal health complications: cross-sectional analysis of data from rural Uttar Pradesh, India - Nabamallika Dehingia; Anvita Dixit; Yamini Atmavilas; Dharmendra Chandurkar; Kultar Singh; Jay Silverman; Anita Raj (BMC, 2020)
Abstract Background This study aims to explore the potential association between unintended pregnancy and maternal health complications. Secondarily, we test whether antenatal care (ANC) and community health worker (CHW) visits moderate the observed association between unintended pregnancy and maternal health complications. Methods Cross sectional data were collected using a multistage sampling design to identify women who had a live birth in the last 12 months across 25 highest risk districts of Uttar Pradesh (N = 3659). Participants were surveyed on demographics, unintendedness of last pregnancy, receipt of ANC clinical visits and community outreach during pregnancy, and maternal complications. Regression models described the relations between unintended pregnancy and maternal complications. To determine if receipt of ANC and CHW visits in pregnancy moderated associations between unintended pregnancy and maternal complications, we used the Mantel-Haenzel risk estimation test and stratified logistic models testing interactions of unintended pregnancy and receipt of health services to predict maternal complications. Results Around one-fifth of the women (16.9%) reported that their previous pregnancy was unintended. Logistic regression analyses revealed that unintended pregnancy was significantly associated with maternal complications- pre-eclampsia (AOR:2.06; 95% CI:1.57-2.72), postpartum hemorrhage (AOR:1.46; 95% CI: 1.01-2.13) and postpartum pre-eclampsia (AOR:2.34; 95% CI:1.47-3.72). Results from the Mantel Haenszel test indicated that both ANC and CHW home visit in pregnancy significantly affect the association between unintended pregnancy and postpartum hemorrhage (p < 0.001). Conclusion Unintended pregnancy is associated with increased risk for maternal health complications, but provision of ANC clinical visits and CHW home visits in pregnancy may be able to reduce potential effects of unintended pregnancy on maternal health.